2003
DOI: 10.1097/01.ju.0000052820.35946.99
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of the Hypospadiac Prepuce and Its Impact On Hypospadias Repair

Abstract: Vascularization of the prepuce is crucial for hypospadias repair. Identification with high precision is achieved by the illumination technique. This method helps create the best vascularized flaps, whether longitudinal, oblique or spiral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…The arterial blood supply of the hypospadiac prepuce is different than normal [3]. Using illumination techniques, Perovic and Radojicic [4] found that preputial axial blood vessels were absent in 30% of hypospadiac patients. They also noted that morphological characteristics of the hypospadiac prepuces correlated with their vascularization [5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The arterial blood supply of the hypospadiac prepuce is different than normal [3]. Using illumination techniques, Perovic and Radojicic [4] found that preputial axial blood vessels were absent in 30% of hypospadiac patients. They also noted that morphological characteristics of the hypospadiac prepuces correlated with their vascularization [5].…”
Section: Discussionmentioning
confidence: 98%
“…The morphology and vascular anatomy of the prepuce have been previously documented in both normal and hypospadiac subjects [4,5]. However, to the best of our knowledge, the microvessel density of hypospadiac prepuce has never been investigated before.…”
Section: Introductionmentioning
confidence: 94%
“…In other words, the actual factors that directly affect blood flow to the prepuce, and the degrees of variation in blood flow are not yet fully recognized and understood (20). Perovic and Radojicic (21) (2003) and Yucel et al (22) (2004) studied vascular distribution in hypospadias patients by using methods such as trans-illumination with a cold light source, microscopic observations after an injection of gelatin and Indian ink, methylene blue injection, and 3-D computer reconstruction after tissue sectioning. Both of those investigators identified four types of prepuce vascular distribution: i) one predominant blood vessel; ⅱ) two predominant blood vessels; ⅲ) two predominant blood vessels with ramus communicans (H-like form); and ⅳ) no predominant blood vessel (net-like form).…”
Section: Discussionmentioning
confidence: 99%
“…Ist die Urethralplatte schmal, so empfiehlt sich die Technik nach Mathieu oder MAGPI. In seltenen Fällen,wenn z.B gleichzeitig eine ausgeprägte Peniskurvatur vorliegt,wird man nach dem Degloving, der Mobilisierung, in manchen Fällen auch Durchtrennung der Uretrhalplatte und der Penisaufrichtung auch eine Onlay-Inselhautlappenuretrhoplastik durchführen müssen [9,10,11,12].…”
Section: Hypospadia Sine Hypospadiaunclassified
“…"schwereren",proximalen Hypospadien muss nach der Penisschaftaufrichtung und der Mobilisierung der Urethralplatte bis zum gesunden Corpus spongiosum die Urethroplastik mit zusätzlichem Gewebe erfolgen.In der Regel handelt es sich hierbei um einen dorsalen Inselvorhautlappen.Dabei dient die Urethralplatte als der Boden und der Vorhautlappen,der als ein Onlay auf die Urethralplatte genäht wird, als das Dach der Neourethra [9,10,11,12]. Ist aber die Vorhaut für die Urethroplastik nicht zu verwenden, wird die Mundschleimhaut erfolgreich eingesetzt [12,13].…”
Section: Hypospadia Sine Hypospadiaunclassified